Answer:
d
Step-by-step explanation: it is that answer because (r+s)t=rt+st is you r answer i did it and i got it correct please mark me as brainlist
5x-8y=1...(1)
3x+6y=-21...(2)
(1)*3:
15x-24y=3...(3)
(2)*5:
15x+30y=-105...(2)
(3)-(2):
15x-24y-(15x+30y)=3-(-105)
15x-24y-15x-30y=108
-54y=108
y=-2
x = 51.98
Step-by-step explanation:
tan 68 = opp/hyp = x/21
or
x = 21×tan68°
= 21(2.475)
= 51.98
Answer:
The missing value is(0,0)
Step-by-step explanation:
The complete question is:
2x+3y=5x-y
Complete the missing value in the solution to the equation.
( ,0)
<u>Solution:</u>
We have given:
2x + 3y = 5x - y
Combine the like terms:
2x-5x= -y-3y
-3x = -4y
Both negative signs will be cancelled out by each other.
So we have,
3x = 4y
We have given y = 0
Then
3x = 4*0
3x= 0
Divide both sides by 3
3x/3 = 0/3
x = 0
y=0
Therefore missing value is(0,0)
Answer:
Step-by-step explanation:
<em>Step 1: Determine quantity per liquid</em>
liquid 1=7/8 cup
liquid 2=9/10 cup
<em>Step 2: Derive expression to calculate total amount of mixture</em>
The expression below can be derived;
T=a+b
where;
T=total amount of mixture
a=total amount of liquid 1
b=total amount of liquid 2
In our case;
a=7/8 cup
b=9/10 cup
replacing;
T=(7/8)+(9/10)=1 31/40 cups
The total amount of mixture=1 31/40 cups